Health and retirement decisions: An update of the literature - Matthias Deschryvere (The Research Institute of the Finnish Economy (ETLA), 2004)
This paper surveys the relation between labour supply and health of the elderly and is based both on major earlier studies and new literature. Most empirical literature on the topic is based on US data, although new European datasets have enabled analysis in several EU countries. The paper complements previous surveys in that it includes those recent European results and overviews most recent developments in micromodelling issues. The quest for unbiased estimates of the effect of health on retirement is characterised by several challenges. A first important challenge is the endogenous character of the relation. A second challenge is the reporting bias that certain health measures may be prone to. The empirical literature surveyed suggests that poor health reduces the capacity to work and has substantial effects on labour force participation. The exact magnitude, however, is sensitive to both the choice of health measures and identification assumptions. For that reason a comparison of health effects between different studies is difficult. An old myth that objective health measures are superior to subjective health measures has proven to be interpreted with care.
Keywords: 330